2007
DOI: 10.1002/smi.1169
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between job burnout and occupational stress among doctors in China

Abstract: The purpose of this study was to explore the status of the job burnout of doctors and the variables associated with this in China. The sample consisted of 543 doctors from three provincial hospitals in China. The Maslach Burnout Inventory‐General Survey (MBI‐GS) was used to measure burnout, and the occupational stress inventory revised edition was used to measure the two dimensions of occupational adjustment (including occupational stress and coping resources). After the statistical testing for validity and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
61
2
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 9 publications
4
61
2
3
Order By: Relevance
“…Drawing a cautious conclusion, this observation is in line with earlier studies [27,28] in which a connection between social support and professional or self-efficacy was found. In this study, physicians in training described the functional – or rather multi-functional – nature of social support; when solving problems the relational and identity functions were also actualized.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Drawing a cautious conclusion, this observation is in line with earlier studies [27,28] in which a connection between social support and professional or self-efficacy was found. In this study, physicians in training described the functional – or rather multi-functional – nature of social support; when solving problems the relational and identity functions were also actualized.…”
Section: Discussionsupporting
confidence: 91%
“…There is some evidence that social support can develop working skills in patient–caregiver relationships [13], and social support can impact managerial learning [26]. Co-worker support is significant for professional efficacy [27] and self-efficacy [28]. Interestingly, social support in the workplace also impacts the choices junior physicians make between specializations [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…In a Sino-Japanese joint venture, Chinese employees often work under Japanese management styles, with emphasis on quality and strict operation standards, and experience conflicts arising from cultural differences, which may lead a higher burnout level. Evidence from earlier studies suggested a positive association between burnout and work-related stress 3,16) . However, there has not been any study on the relationship between occupational stress, burnout and turnover intention among employees in Sino-Japanese joint ventures in the literature.…”
mentioning
confidence: 97%
“…One explanation of why employees adopt external standards without fully identifying with them is a strong and internalised ethic of responsibility [13]. Hence, a strong internalised work ethic among professional groups could cause the development of burnout [27].…”
Section: Discussionmentioning
confidence: 99%
“…The strong and internalised ethic of responsibility among professionals might result in adoption of external standards without fully identifying with them, which in turn can lead to health problems [13]. In nursing, the general norm is to be selfless and to put the needs of others in the first place, doing whatever it takes to help the patients.…”
Section: Introductionmentioning
confidence: 99%